The Influence of Confusian Ethics and Collectivism on Whistleblowing Intention - Klemensia Erna Christina Sinaga (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
Business development in Indonesia cannot be separated from the touch of the Chinese ethnicity. Chinese ethnicity has spread to almost all parts of Indonesia, cannot be underestimated, and has become one of the business icons whose business is growing in Indonesia. Research on whistleblowing associated with Confucian ethics in Indonesia is attractive due to the increasing influence of Chinese ethnicity in the political and business sectors. This study examines the influence of Confucian ethics and Collectivism on whistleblowing intentions. The sampling technique in this study used a purposive sampling technique, namely a sampling method based on specific considerations. This research focuses on Chinese private employees in Indonesia. All respondents will be asked to answer a questionnaire directly or via a printed or Google form link. The statistical tool used in this study is multiple regression. The results showed that Confucian Ethics affected Whistleblowing Intentions, while Collectivism did not affect Whistleblowing Intentions. This research is expected to fill the void in the literature regarding whistleblowing and Confucian ethics in Indonesia.